2019
DOI: 10.20870/oeno-one.2019.53.1.2366
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin content and composition in four red winegrape cultivars (Vitis vinifera L.) under variable irrigation

Abstract: Aim: The aim of this study was to determine and compare anthocyanin content and profile under variable irrigation regimes in four red grape cultivars (Vitis vinifera L.), the Greek indigenous cvs. Agiorgitiko and Xinomavro, alongside Syrah and Grenache noir.Methods and results: Three irrigation treatments were applied in a 6-year-old vineyard comprising all four varieties in a block design, starting at bunch closure (E-L 32) through harvest of 2012 and 2013: full irrigation (FI) at 100% of crop evapotranspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…In this context, monitoring berry volume variations and sugar accumulation in response to irrigation could provide critical information to better assess vineyard response to water deficit in combination with other factors. This is even more important considering that fruit composition respond differently to water stress for different varieties, as shown for Cabernet-Sauvignon vs Shiraz (Hochberg et al, 2015) or for Greece's autochthonous varieties Agiorgitiko and Xinomavro (Theodorou et al, 2019) or Italian grape cultivars Montepulciano and Sangiovese (Palliotti et al, 2014). Those results illustrate how changes in secondary metabolism in response to water stress are specific to each cultivar, therefore irrigation threshold and frequency could be defined according to the unique varietal specific response of fruit composition to water stress.…”
Section: Recent Scientific Advances Regarding Irrigation Intervalsmentioning
confidence: 79%
See 2 more Smart Citations
“…In this context, monitoring berry volume variations and sugar accumulation in response to irrigation could provide critical information to better assess vineyard response to water deficit in combination with other factors. This is even more important considering that fruit composition respond differently to water stress for different varieties, as shown for Cabernet-Sauvignon vs Shiraz (Hochberg et al, 2015) or for Greece's autochthonous varieties Agiorgitiko and Xinomavro (Theodorou et al, 2019) or Italian grape cultivars Montepulciano and Sangiovese (Palliotti et al, 2014). Those results illustrate how changes in secondary metabolism in response to water stress are specific to each cultivar, therefore irrigation threshold and frequency could be defined according to the unique varietal specific response of fruit composition to water stress.…”
Section: Recent Scientific Advances Regarding Irrigation Intervalsmentioning
confidence: 79%
“…These examples illustrate the dependency of vineyard architectural features on the regulation of leaf and berry temperature. Several studies with different cultivars, showed that berry temperature increases when water stress increases and that this sensitivity to high temperatures is genotype dependent (Carvalho et al, 2016;Theodorou et al, 2019;Zarrouk et al, 2016a). As shown by several studies, berry temperature is of crucial importance for the synthesis and degradation of quality determining compounds.…”
Section: Effect Of Hydraulic Structure Light and Temperature On Tranmentioning
confidence: 97%
See 1 more Smart Citation
“…Anthocyanins composition (the relative portion of individual anthocyanins, the ratio of di-oxygenated vs. tri-oxygenated side-ring forms, the ratio of acylated vs. non-acylated derivatives, etc.) is variable among grapevine cultivars (Monagas et al, 2003 ; Theodorou et al, 2019 ) and can be modified by abiotic factors as discussed in later sections.…”
Section: Grape Berry Phenolicsmentioning
confidence: 99%
“…The presence of acylated anthocyanins may be very important for wine color since they participate in intra/molecular co/pigmentation processes, thus increasing the intensity of the wine color [15] . Also, non‐acylated anthocyanins are more sensitive to oxidation reactions in berries, while acylated ones represent a more stable form of anthocyanins to oxidative effects increasing that way color stability [16] . According to some authors, [7,17] the percentage of acylated anthocyanins and in particular, those in form of acetates, are those that most contribute to varietal differences.…”
Section: Resultsmentioning
confidence: 99%